2020
DOI: 10.7556/jaoa.2020.004
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Perceived Stress, Sleep Quality, and Smartphone Use: A Survey of Osteopathic Medical Students

Abstract: Context: Burnout is a psychological syndrome that results from prolonged exposure to stressful work activities and includes 3 dimensions: emotional exhaustion (EE), depersonalization (DP), and low sense of personal accomplishment (PA). Burnout is a widespread problem in numerous professions but is particularly high among medical students, residents, and early-career physicians compared with college graduates of similar age. However, minimal research has addressed burnout in osteopathic medical students. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
(57 reference statements)
2
18
1
Order By: Relevance
“…Perceived pressure and sleep were related to burnout among faculty at doctoral research universities (56). A recent cross-sectional study conducted among osteopathic medical students also found that higher perceived stress and poorer sleep quality were associated with all three dimensions of burnout (57). Results of our study reveals that perceived stress might not only exert a direct effect on burnout, but could also have indirect effect on burnout through sleep quality, indicating that nurses with higher levels of perceived stress tend to report poorer sleep quality and there is an increased risk on the development of burnout.…”
Section: Discussionmentioning
confidence: 96%
“…Perceived pressure and sleep were related to burnout among faculty at doctoral research universities (56). A recent cross-sectional study conducted among osteopathic medical students also found that higher perceived stress and poorer sleep quality were associated with all three dimensions of burnout (57). Results of our study reveals that perceived stress might not only exert a direct effect on burnout, but could also have indirect effect on burnout through sleep quality, indicating that nurses with higher levels of perceived stress tend to report poorer sleep quality and there is an increased risk on the development of burnout.…”
Section: Discussionmentioning
confidence: 96%
“…The study on a group of 385 osteopathic medical students performed by Brubaker et al. (2020) in 2018 detected that higher smartphone addiction scores are associated with higher emotional exhaustion and depersonalization but are not related with the personal achievement. Hence, the mobile phone addiction may have connection with the feeling of exhaustion by the work and impassive emotions towards others.…”
Section: Discussionmentioning
confidence: 99%
“…Additional demographic and health characteristics are presented in Table 1. Overall, the demographic data in this study were similar to findings from a larger research study with the same first-and second-year students (age = 24.9 ± 2.3, t = .3065 p = .759; 52.3% women (n = 139), χ 2 = .0467, p = 0.829; 73.3% White (n = 195), χ 2 = .630, p = 0.529; BMI = 24.9 ± 4.5, .630, p = 0.529) on burnout, sleep quality, and smartphone addiction [30] as well as the general population of first-and second-year students (n = 495; age = 25.0 ± 2.2; 52.7% women (n = 257); 76% White (n = 376); BMI = unknown) from this institution.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, smartphone overuse is associated with higher burnout scores, in particular emotional exhaustion and depersonalization, in medical students [ 30 ]. This may be particularly relevant considering the percentages of medical students exhibiting smartphone addiction across the world (29.8% in Anhui Province, China [ 31 ]; 39.9% in Delhi, India [ 28 ], 36.5% in Jeddah, Saudi Arabia [ 32 ], 22.3% in Ohio, United States [ 30 ]). Medical students experience disproportionately higher burnout rates compared to similarly aged college graduates [ 4 ].…”
mentioning
confidence: 99%